Marginal zinc deficiency increases oxidative DNA damage in the prostate after chronic exercise - Song, Yang (2009)
Approximately 12% of Americans do not consume the recommended level of zinc and could be at risk for marginal zinc deficiency. Zinc functions in antioxidant defense and DNA repair and could be important for prostate health. We hypothesized that marginal zinc deficiency sensitizes the prostate to oxidative stress and DNA damage. Rats were fed a zinc-adequate (ZA; 30 mg Zn/kg) or marginally zinc-deficient (MZD; 5–6 mg Zn/kg) diet for 6 weeks. MZD increased p53 and PARP expression but no change in 8-hydroxy-2′-deoxyguanosine levels was detected. To examine the susceptibility to exogenous oxidative stress, rats fed a ZA or MZD diet were assigned to exercising (EXE) or sedentary (SED) groups for 9 weeks. MZD or EXE alone did not affect oxidative DNA damage in the prostate; however, combined MZD + EXE increased DNA damage in the dorsolateral lobe. PARP and p53 expression was not further induced with MZD + EXE, suggesting that MZD interferes with DNA repair responses to stress. Finally, the addition of phytase to the MZD diet successfully restored zinc levels in the prostate and decreased DNA damage back to ZA levels. Overall, this study suggests that marginal zinc deficiency sensitizes the prostate to oxidative stress and demonstrates the importance of maintaining optimal zinc nutrition in physically active populations.